2020
DOI: 10.1016/j.jvs.2020.04.494
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular examination should also include peripheral arterial evaluation for COVID-19 patients

Abstract: Recently, a small number of patients have presented with systemic intra-arterial thrombosis and a diagnosis of SARS-CoV-2. There is some evidence to suggest that this may occur, with a small series reporting ischemic strokes in patients in intensive care units. 5 In our experience, patients presenting with limb-threatening ischemia and SARS-CoV-2 have had no other clear reason for development of intra-arterial thrombosis. Management has been dictated primarily by the severity of the organ dysfunction. A conse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 4 publications
0
14
0
Order By: Relevance
“…Five cohort studies ( n = 537 patients) reported data on the incidence of AT in severe/critically ill ICU-admitted COVID-19 patients, with the incidence ranging from 2.7%–8%. 11 , 19 , 24 , 28 , 34 The pooled incidence of AT across these 5 studies was 4.4% (95% confidence interval 2.8–6.4), with no interstudy heterogeneity observed (I2 = 0%, Cochran's Q = 3.908; P = 0.419; Fig. 2 ).…”
Section: Resultsmentioning
confidence: 95%
See 3 more Smart Citations
“…Five cohort studies ( n = 537 patients) reported data on the incidence of AT in severe/critically ill ICU-admitted COVID-19 patients, with the incidence ranging from 2.7%–8%. 11 , 19 , 24 , 28 , 34 The pooled incidence of AT across these 5 studies was 4.4% (95% confidence interval 2.8–6.4), with no interstudy heterogeneity observed (I2 = 0%, Cochran's Q = 3.908; P = 0.419; Fig. 2 ).…”
Section: Resultsmentioning
confidence: 95%
“…A total of 27 studies describing arterial thrombotic events in 90 COVID-19 patients were included. 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 The majority of the studies were from Europe (23 studies; France: 8, Italy: 7, Spain: 4, the United Kingdom: 3, and the Netherlands: 1), whereas the rest were from North America (the United States of America: 3 and Canada: 1). Of the included studies, 5 were cohort, 5 were case series, and the rest were case reports.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Since the first case detected in late 2019 in China, a fast worldwide expansion confirms it. The current knowledge of the disease describes mostly on a severe acute respiratory syndrome (SARS-CoV-2) while many other clinical descriptions of the disease have also been reported, such as peripheral arterial thrombosis, 1,2 myocarditis, or central nervous system affections.…”
Section: Introductionmentioning
confidence: 99%